Modern women attack a postfeminist study of the portrayal of women in whitening lotion commercials in the Philippines - Rollorata, Ronessa Eval 1991- (2012)
"This thesis introduces the concept of postfeminism in understanding the bigger picture of the portrayal of women in existing whitening lotion TV advertisements in the Philippines. Television advertisements are regarded as powerful instruments in affecting the lives and behaviors of the Filipinos. Yet, it is always criticized for propagating highly stereotyped images of men and women. In our country, advertisements of whitening products are considered one of the most influential in affecting the Filipino audience. Through the years, these kinds of advertisements have coordinated progressive ideas about women giving them a sense of false empowerment and making the audience believe this illusion. My study explores the past and recent portrayal of women in various whitening lotion commercials shown in the Philippines in the years of 2004 to 2011. I aim to determine how much has changed. Using postfeminism as my main framework, I set out to find the mechanisms behind the shift in the representation of women, from the traditional weak and passive to the modern liberated and empowered, and see its connection to media and society at large. To ground my research, I present a view of related literature that discusses different views and assumptions about postfeminism. I employ the most valid points in those studies and pick the most appropriate to express my own take to explain this phenomenon and uncover the truth in media's notion of women's liberation. Based on my findings, I then conclude that the portrayal of women in recent commercials is moving towards the postfeminist representations."